Pengaruh Penambahan Aspal Buton pada Aspal Pen 60/70 terhadap Sifat Mekanik pada Lapisan Permukaan AC-WC - Shilvhanie Usman; Yenni Darvina; Leni Aziyus Fitri; Fandi Oktasendra (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to determine the effect of adding Buton Asphalt on the mechanical properties of Asphalt Concrete – Wearing Course (AC-WC) mixtures based on Marshall test parameters. The variations of asphalt content used were 0%, 2%, and 5%. Each variation was tested using the Marshall method to obtain the values of Stability, Flow, Void in Mix (VIM), Void in Mineral Aggregate (VMA), Void Filled with Asphalt (VFA), and Marshall Quotient (MQ). The results show that the addition of Buton Asphalt affects the improvement of the mixture characteristics. The highest stability value was obtained at 5% Buton Asphalt content, which was 1,074 kg, while the lowest flow value was also found at 5%, which was 2.48 mm, indicating that the mixture becomes stiffer and more stable. The VIM value decreased from 4.7% at 0% content to 4.2% at 5% content, indicating that the air voids in the mixture became smaller. The VMA value also decreased from 16.2% at 0%, 15.8% at 2%, and 15.1% at 5%, while the VFA value increased from 71% to 72.18%. The highest Marshall Quotient (MQ) value was obtained at 5% Buton Asphalt content, which was 433 kg/mm, indicating that the mixture has better stiffness and resistance to deformation. Based on these results, it can be concluded that the addition of 5% Buton Asphalt provides the best mixture characteristics for the AC-WC layer.